2014
DOI: 10.1371/journal.pone.0091302
|View full text |Cite
|
Sign up to set email alerts
|

Proteins Involved in Motility and Sperm-Egg Interaction Evolve More Rapidly in Mouse Spermatozoa

Abstract: Proteomic studies of spermatozoa have identified a large catalog of integral sperm proteins. Rapid evolution of these proteins may underlie adaptive changes of sperm traits involved in different events leading to fertilization, although the selective forces underlying such rapid evolution are not well understood. A variety of selective forces may differentially affect several steps ending in fertilization, thus resulting in a compartmentalized adaptation of sperm proteins. Here we analyzed the evolution of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 64 publications
5
38
0
Order By: Relevance
“…Leucine-rich repeat containing (Lrrc) genes have diverse biological roles; therefore, we also will not speculate on any correspondence between these two genes. As expected given our experimental design, there was no concordance between our 42 genes and those found to be under positive selection in a recent study on mouse spermatozoa proteins (Vicens, Luke & Roldan, 2014). …”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Leucine-rich repeat containing (Lrrc) genes have diverse biological roles; therefore, we also will not speculate on any correspondence between these two genes. As expected given our experimental design, there was no concordance between our 42 genes and those found to be under positive selection in a recent study on mouse spermatozoa proteins (Vicens, Luke & Roldan, 2014). …”
Section: Resultssupporting
confidence: 70%
“…In addition, the epididymal transcriptome of M. musculus shows evidence for positive selection among epididymis-specialized genes that are secreted, which the authors attribute to their putative evolutionary importance (Dean, Good & Nachman, 2008). Moreover, a recent analysis for sperm genes from multiple mouse strains found that sperm proteins involved in both motility and in sperm-egg interactions show signatures of positive selection, potentially facilitating evolutionary mechanisms for sperm-competition and sexual conflict (Vicens, Luke & Roldan, 2014). We therefore propose that both the inherently costly nature of producing ejaculate and the rapid evolution of genes in murine testes, epididymis, and sperm would be ideal for desert rodents to evolve ejaculate adaptations to limited water-availability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, rapid evolution of sperm genes appears to be the most reasonable 425 explanation for the breakdown of reciprocal relationships (see below). This conclusion is consistent with 426 a diverse body of evidence that supports the influence of positive selection on male reproductive genes 427 [62,65], including those functioning in sperm [43,[66][67][68]. We note that we cannot rule out the influence 428 of de novo creation but it is currently difficult to assess the contribution of this mechanism to the overall 429…”
Section: Rapid Evolution Of Genetic Architecture 408supporting
confidence: 72%
“…16). Based on nucleotide sequences of different mouse strains and species, Vicens et al 18. found higher proportions of genes with signals of positive selection in groups linked to sperm-egg interaction and sperm motility than in four other categories.…”
Section: Resultsmentioning
confidence: 99%